(untitled) (KYAMC Journal, 2013)
Carotid atherosclerosis is associated with ischemic stroke. It is common in the elderly and the condition can be controlled or improved by drugs. In order to find out the role of antioxidant vitamins (beta carotene [USP 6 mg], Vitamin C [BP 200 mg] and Vitamin E [BP 50 mg]) and aspirin, aspirin and ACE- inhibitor (Ramipril) or aspirin alone in prevention of ischaemic stroke due to plaque in or near carotid artery bifurcation diagnosed by carotid color duplex ultrasonography and patients attended in Dhaka Medical College Hospital were studied to justify that these are effective. DOI: http://dx.doi.org/10.3329/kyamcj.v2i1.13512 KYAMC Journal Vol.2(1) 2011 pp.96-108